Causality between financial development and foreign direct investment in Asian developing countries - Huy Tiet Pham; Christopher Gan; Baiding Hu (Journal of Risk and Financial Management, 2022)
This study investigated the linkages between foreign direct investment (FDI) and financial development measured by banks and stock markets in 30 Asian developing countries from 1986 to 2019. We used a bivariate model with Granger causality tests to test the reverse causality between FDI and financial development and multivariate models with the system generalized method of moments (GMM) estimator to identify how one factor affected the other. Our Granger test results showed a bidirectional linkage between FDI and financial development. Using the system GMM estimator, we showed that greater financial development drew more inward FDI to host countries. Similarly, local financial markets benefited from FDI by improving capital mobilization and financial services and products to intensify economic activity. Our findings suggest that, to attract FDI, policymakers should improve local banks and the stock market environment with strong institutional backgrounds to enhance foreign investors' confidence and provide incentives to increase cross-border investments in host economies.
Keywords: 650; Granger causality; Asian developing countries; financial development; foreign direct investment; system GMM